Testicular Biometry and its Relationship with Body Weight and Semen Parameters of Sirohi and Jamnapari Bucks - Alam, Kabir; Srivastava, Sushant; Kumar, Rajesh; Saurabh,; Verma, Abhishek Kumar; Verma, Sanjeev Kumar; Jaiswal, Ankit; Verma, Hukum Chandra (The Indian Journal of Animal Reproduction, 2024)
The objective of this study was to examine the relationship between testicular biometry and body weight, as well as semenparameters (ejaculate volume and total sperm concentration/ejaculate) in Sirohi and Jamnapari bucks. A total of sixbucks (2 Sirohi and 4 Jamnapari) were chosen for testicular biometry. The average body weight for Sirohi and Jamnaparibucks was 48.7±3.0 kg and 38.82±1.3 kg, respectively. Similarly, the average scrotal circumference was measured to be27.35±0.57 cm for Sirohi bucks and 25.11±0.4 cm for Jamnapari bucks. The semen volume of Sirohi and Jamnapari buckswas recorded to be 1.15±0.1 ml and 0.79±0.0 ml, respectively. Additionally, the total sperm concentration per ejaculatewas found to be 3120±165.6 million for Sirohi bucks and 2263±101.0 million for Jamnapari bucks. There was a positivecorrelation between scrotal circumference and body weight in both the breeds.The measurements of the left testis exceeded those of the right testis at the same age. The semen volume and total spermconcentration per ejaculate showed a strong and statistically significant correlation with almost all testicular indices (p
Keywords: Testicular biometry; Sirohi; Jamnapari; buck semen; scrotal circumference